Multi-species single-cell transcriptomic analysis of ocular compartment regulons - Pradeep Gautam (Nature Portfolio, 2021)
A comprehensive analysis of the ocular networks among various tissues is necessary to understand eye physiology in health and disease. Here the authors present a multi-species single-cell transcriptomic atlas consisting of cells of the cornea, iris, ciliary body, neural retina, retinal pigmented epithelium, and choroid.